Analysis of Pro-Environmental Behavior (PEB) through Motivation of Senior High School Students - Desi Eka Nur Fitriana; Mieke Miyarsah; Rusdi Rusdi (BIODIK, 2019)
Proenvironmental behavior is a behavior that seeks to minimize negative impacts on the environment which could be influenced by several factors, one of which is motivation. This study aims to analyze the direct effect of motivation on proenvironmental behavior. This research was conducted using quantitative approach with causal survey method and analyzed using path analysis. The number of samples used as respondents is 200 students from class XI MIA SMAN 1 Tangerang Regency. Based on the results, a conclusion could be made that there is a positive direct effect of personality on proenvironmental behavior with a path analysis coefficient of 0.159. There is a positive direct effect of motivation on proenvironmental behavior with a path coefficient of 0.486. Keywords: Motivation, Pro Environment Behavior, Path Analysis. Abstrak. Perilaku pro lingkungan adalah perilaku yang berupaya meminimalkan dampak negatif terhadap lingkungan yang dipengaruhi oleh beberapa faktor, salah satunya adalah motivasi. Penelitian ini bertujuan untuk menganalisis pengaruh langsung motivasi terhadap perilaku pro lingkungan. Penelitian ini dilakukan dengan menggunakan pendekatan kuantitatif dengan metode survei kausal dan dianalisis menggunakan analisis jalur. Jumlah sampel yang digunakan sebagai responden adalah 200 siswa kelas XI MIA SMAN 1 Kabupaten Tangerang. Berdasarkan hasil pengujian hipotesis dapat disimpulkan bahwa ada pengaruh langsung positif kepribadian terhadap perilaku proenvironmental dengan koefisien analisis jalur sebesar 0,159. Ada pengaruh langsung positif dari motivasi pada perilaku pro lingkungan dengan koefisien jalur 0,486. Kata Kunci: Motivasi, Perilaku Pro Lingkungan, Analisis Jalur